2020
DOI: 10.3389/fnagi.2020.00029
|View full text |Cite
|
Sign up to set email alerts
|

Intentional Switching Between Bimanual Coordination Patterns in Older Adults: Is It Mediated by Inhibition Processes?

Abstract: Frontiers in Aging Neuroscience | www.frontiersin.org February 2020 | Volume 12 | Article 29 Temprado et al. Bimanual Switchingat least to trigger the early phase of switching. They also support the hypothesis that inhibition processes are more involved in maintaining the AP pattern and switching to the IP pattern. Finally, age-related changes in switching times seem to be prominently mediated by alterations of inhibition processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 44 publications
4
24
0
Order By: Relevance
“…We did not find evidence for inhibitionspecific contributions to complex motor performance in this sample. In the correlated factors model, the inhibition factor showed a positive, but non-significant relationship with motor performance, which is broadly consistent with earlier reports based on findings on a single inhibition task [65]. In the bifactor model, the "inhibition"-specific factor mainly captured variability in NST (standardized factor loading: .59) and less from other inhibition tasks (AT: .02, SST: .38), and hence might not have reflected inhibition optimally.…”
Section: Discussionsupporting
confidence: 90%
“…We did not find evidence for inhibitionspecific contributions to complex motor performance in this sample. In the correlated factors model, the inhibition factor showed a positive, but non-significant relationship with motor performance, which is broadly consistent with earlier reports based on findings on a single inhibition task [65]. In the bifactor model, the "inhibition"-specific factor mainly captured variability in NST (standardized factor loading: .59) and less from other inhibition tasks (AT: .02, SST: .38), and hence might not have reflected inhibition optimally.…”
Section: Discussionsupporting
confidence: 90%
“…On the one hand, cognition modulates functional interactions between the different components of the BMBS, thereby allowing to shape the emerging behavioral patterns [e.g. (Zanone and Kelso, 1992;Monno et al, 2002;Taylor et al, 2018;Temprado et al, 2020)]. On the other hand, cognition supports the attunement of behavior to the perceptual-motor workspace by supervising how the individual does something somewhere (Araujo, 2009), that is, how it attains a functional relationship with the world by virtue of changes in information-movement coupling [e.g.…”
Section: The Ecological Dynamics Approachmentioning
confidence: 99%
“…It can be directly or indirectly assessed through dynamical markers (Sleimen-Malkoun et al, 2014), as, for instance, directly through (i) the repertoire of behavioral patterns (Sleimen-Malkoun et al, 2013Temprado et al, 2020) and/or of execution strategies [e.g. (Poletti et al, 2016)] that are available and effectively used by the performer; and (ii) the dynamics of switching between behavioral patterns and strategies that are observed when task constraints are increased [e.g.…”
Section: The Ecological Dynamics Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed larger activation of the prefrontal areas during motor tasks in older adults, which suggested that executive functions become more involved in complex movement control (e.g., interlimb coordination) compared to younger subjects [ 20 , 21 ]. Convergent evidence also suggested a strong link between age-related alteration of executive functions and deficits in gait, posture [ 22 ], and bimanual coordination [ 23 ]. According to this theoretical framework, it can be hypothesized that, in older adults, motor skills training involves more cognitive resources than in younger adults and could, therefore, be particularly appropriate to improve cognitive functions [ 24 ].…”
Section: Introductionmentioning
confidence: 99%